Adaptation of the Centers for Disease Control Surgical Wound Classification System for Orthopaedic Trauma Surgery. Issue 5 (May 2022) - Scolaro, John A.; Agel, Julie; Marmor, Meir; Dumpe, Jarrod; Karam, Matt; Kellam, James; Meinberg, Eric; Munz, John; Nguyen, Mai; Soles, Gillian; Stinner, Daniel; Marecek, Geoffrey S.
Abstract : Objectives: To evaluate a proposed orthopaedic-specific surgical wound classification system (SWCS) and the current Centers for Disease Control (CDC) system in a series of detailed clinical vignettes and to identify the degree of satisfaction with CDC SWCS and desire for institution of an orthopaedic-specific SWCS. Methods: Forty-five clinical vignettes and a 5-question survey were distributed to current and past members of the Orthopaedic Trauma Association's Classification Committee. Respondents were asked to provide wound class for each vignette using the CDC system and orthopaedic-specific SWCS. Results: The orthopaedic-specific and CDC SWCS had interclass correlations of 0.95 and 0.91, respectively. When the systems were compared, in 34% of cases, there was no grade change; in 63% of cases, the wound was graded higher using the orthopaedic-specific SWCS. When only the procedure was changed between vignettes, wound classification was infrequently affected. There was near universal dissatisfaction with the CDC SWCS and desire for an orthopaedic-specific system. Conclusions: Both the CDC SWCS and orthopaedic-specific SWCS have excellent interobserver reliability. Incorporation of orthopaedic-specific language affects wound classification. There is low satisfaction with the current CDC SWCS and a desire exists for further development and validation of an orthopaedic-specific SWCS.